Linking co-creation to modularity to respond to consumers expectations and improve production efficiency - Martins, Paulo; Miguel, Rui; Pina, Liliana; Pereira, Madalena (Wydawnictwo Politechniki Łódzkiej, 2022)
This paper aims to understand what the consumers intend to co-create, secondly if modular co-created products can respond to consumers’ expectations and thirdly, if the process and production efficiency could be improved, even for small orders, when based on modular products. This data will serve as a basis for understanding what methods or processes can be applied and benefit consumers, brands and the supply chain. A single closed question was made to the consumers. In addition, one open question was made to the fashion designers and another to the supply chain experts. These were created based on a literature review, study question, and propositions. The findings show that the consumers prefer to co-create full fashion products. Fashion designers and supply chain experts were unanimous about the improvement of the process and production efficiency due to modular products, even when producing small orders. Although, when responding to the consumers’ expectations, some concerns were raised by the fashion designers. This paper will enable, in the future, the development of a consumer, brand and supply chain cocreation streamlined framework.
Keywords: co-creation; modularity; consumer; supply chain; production; efficiency; współtworzenie; modułowość; konsument; łańcuch dostaw; produkcja; efektywność